Word Bank: An Introductory Dictionary - White, Malcolm and Seccombe, Malcolm (HarperCollins Publishers Ltd, 2002)
Word Bank is an introductory dictionary which offers practical help to students trying to improve their reading and writing skills$1! =s
Keywords: Facts / Dictionaries